PROGRAM NONLINEAR FUZZY - Khairudin, Khairudin (MATEMATIKA, 2004)
Nonlinear programming problems have not been developed yet and still to be attention for research just recently. In this paper will be introduced simple fuzzy nonlinear programming problem with any membership nonlinear function, like proposed by Wang and Tang in their paper at 1995 to 1997(Gen and Cheng, 2000). Via defuzzyfication process by Belmann and Zadeh (1970) so that will be improved that fuzzy nonlinear programming problem can be transformed into conventional nonlinear problems.